Pefloxacin induced changes in serotonergic innervation and mast cell number in rat salivary glands. (2nd September 2020) - Skopkó, Boglárka Emese; Deák, Ádám; Matesz, Clara; Kelentey, Barna; Bácskai, Tímea
Abstract: Pefloxacin is a second-generation fluoroquinolone antibiotic. Besides its advantageous characteristics, side effects including the hypofunction of salivary glands, decreased saliva production, and peripheral neuropathy were observed during the administration of pefloxacin. The aim of this study was to investigate the changes in the number of serotonergic immunoreactive fibers and mast cells after pefloxacin treatment in the parotid and sublingual glands of rats to detect the possible neurotoxic effect of pefloxacin. The adult female rats were treated with intraperitoneal (i.p.) injection of pefloxacin for three or seven days (at a concentration of 20 mg/100g body weight) and the serotonergic innervation pattern along with the change in mast cell number were evaluated by using histochemistry and immunohistochemistry in the parotid and sublingual glands. We found that a three-day treatment significantly increased the number of immunoreactive serotonergic nerve fibers, but after a seven-day treatment the number of serotonin positive nerve fibers decreased almost to values of the control group. The alteration of mast cell number was parallel with the changes of the serotonin positive fibers during the treatment. These results suggest that pefloxacin treatment can modify the finely controlled communication between the immune- and the peripheral nervous systems, resulting neurogenic inflammatory process. The background of this process is the altered serotonergic innervation and the increased number of activated mast cells releasing different mediators for example histamine, which can finally lead to reduced number of serotonin positive nerve fibers after a seven-day treatment of pefloxacin leading to atrophy and hypofunction of the salivary glands.